THE SHIFT OF THE SCIENCE DICHOTOMY PARADIGM TOWARDS SCIENCE INTEGRATION - Yatusa'dah, Khulaefi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Historically, it can be seen that the Islamic world has reached its heyday, this is marked by the rise of science and philosophy. In the next period Islam experienced a period of decline or did not develop, many factors that influenced this, one of which was the dichotomy in science. The dichotomy is the separation between religious knowledge and general science. This separation advances general knowledge and puts aside religious knowledge. In another situation came the notion of secularism which increasingly gave birth to religious knowledge. Secularism assumes that religion is an obstacle to progress, so they separate themselves from religion in an effort to develop science. In the next period, the ideology of secularism achieved success in science. Meanwhile, Muslims are just beginning to realize the necessity to rise again, but in this effort, what is presented to them is the ideology of secularism which they consider to be incompatible with the teachings of Muslims. So that the Islamic leaders emerged who made efforts to integrate knowledge or what could be called the Islamization of science, this aims so that western science can be consumed by Muslims whose ending is to realize the goals of Islam. Islam does not consider there is a difference between religious knowledge and general knowledge. both must go hand in hand, this is proven that in the Qur'an there are many verses that explain natural phenomena, that means there is an order to conduct studies with tools to prove knowledge that comes from revelation, while making tools is included in the realm of general science. Keywords: dichotomy, secularism, and integration or Islamization of knowledge Abstrak Secara historis dapat diketahui bahwa dunia Islam Pernah menggapai masa kejayaan, hal ini ditandai dengan maraknya ilmu pengetahuan dan filsafat. Dalam masa berikutnya Islam mengalami masa kemunduran atau tidak berkembang, banyak faktor yang mempengaruhi hal tersebut salah satunya adalah adanya dikotomi dalam keilmuan. Dikotomi adalah pemisahan antara ilmu agama dengan ilmu umum. pemisahan tersebut memajukan ilmu umum dan menyampingkan ilmu agama. Dalam situasi yang lain datanglah faham sekularisme yang semakin menganak tirikan ilmu agama. Faham sekularisme menganggap bahwa agama adalah penghambat kemajuan, sehingga mereka memisahkan diri dari agama dalam upaya pengembangan ilmu pengetahuan. Pada masa berikutnya faham sekuarisme mencapai kejayaan dalam ilmu pengetahuan. Sedangkan umat Islam baru mulai menyadari akan keharusan untuk bangkit kembali, tetapi dalam upaya tersebut yang disuguhkan kepada mereka adalah faham sekularisme yang dianggapnya tidak sesuai dengan dotrin umat Islam. Sehingga muncullah para tokoh Isalam yang melakukan upaya integrasi ilmu atau bisa disebut islamisasi ilmu pengetahuan, hal ini bertujuan agar ilmu pengetahuan barat dapat dikonsumsi oleh umat Islam yang endingnya adalah mewujudkan tujuan agama Islam. Ilmu agama dan ilmu umum harus berjalan beriringan yang saling berkaitan satu sama lain. Kata kunci : dikotomi, sekularisme, dan integrasi atau islamisasi ilmu